Time-resolved experiment of IR-induced anion reaction dynamics - An, Sejun (2020)
A pump-probe experiment with the picosecond laser system was designed to reveal the vibrational mode-effect on the anion reaction dynamics. Vibrational excitation by IR pulse initiates the reaction of anions, such as autodetachment, electron-transfer, and isomerization. Visible pulse after IR pulse can detach the electron from the reaction product. Reaction rate, yield, energy, and isomer distribution can be obtained from the kinetic energy distribution of detached electron. Anion source, mass selection system, VMI photoelectron spectrometer, and high-intensity mid-IR[1] have been prepared for this IR-Vis pump-probe experiment.